Outcome of pregnancy in women with splenomegaly - AbdelAziem A. Ali; Israa Badr Eldin (BMC Pregnancy and Childbirth, 2023)
Abstract Background The spleen is a lymphopoietic organ, contains almost one quarter of the body’s lymphocytes. Method This was a prospective cross sectional study, carried out at Kassala hospital, Sudan between 1st of May 2019 to 30th of April 2020. The objective of this study was to investigate the outcome of pregnancy in women with splenomegaly. A total coverage of 57 women with splenomegaly were approached among all pregnant women attending the hospital and asking for care. An enlarged spleen detected by palpation and subcategorized into mild, moderate and severe one according to its length below the left costal margin using Ultrasound. Data was collected using structured questionnaire. Means and proportions were compared between the groups of the study-using student and x 2 test, and P < 0.05 was considered significant. Results The most predominant type of splenomegaly was massive (50.9%) splenomegaly. The reported obstetric complications among the investigated women include: intrauterine growth restriction (19.3%), preterm labor ((17.5%), miscarriage (12.3%) and stillbirth (3.5%). Out of 50 patients their pregnancy progressed to delivery, three patients developed primary hemorrhage requiring blood transfusion with ≥ 2 units of blood. Respiratory distress syndrome (RDS), acute tachypnea of the newborn and stillborn babies were observed in 18%, 6% and 4% respectively. Higher proportion of women with poor obstetric outcomes was reported in cases of massive splenomegaly in comparison with other types. Conclusion The study showed significant association between adverse obstetric outcomes and massive splenomegaly. Thus, it is important to consider splenomegaly as one of the factors making the pregnancy high-risk one.